2004
DOI: 10.1023/b:trop.0000042862.50129.a1
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Calves and Reproductive Performance of Cows in Commercial Dairy Farms in and Around Addis Ababa, Ethiopia

Abstract: A study was conducted at five locations to determine the survival rate of calves and to estimate the performance level of improved dairy cows under commercialized farming systems in Ethiopia. Seven hundred and one calves born from 1997 to 1999, and 797 cows were included in the study. Cumulative calf/heifer survival at 360, 540 and 720 days was 80%, 76% and 70%, respectively. Number of services per conception averaged 2 while mean age at first service and days open were 850+/-18 and 192+/-11 days, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 2 publications
4
10
2
Order By: Relevance
“…In agreement with a previous report, season had a significant influence on NSC (Asseged and Birhanu 2004), and cows served for the first time during rainy season had higher NSC than those cows that were inseminated for the first time during other seasons. This is probably due to the inability to detect estrus signs and the subsequent failure of services, as a result of confinement of the cows in-housed during the rainy season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with a previous report, season had a significant influence on NSC (Asseged and Birhanu 2004), and cows served for the first time during rainy season had higher NSC than those cows that were inseminated for the first time during other seasons. This is probably due to the inability to detect estrus signs and the subsequent failure of services, as a result of confinement of the cows in-housed during the rainy season.…”
Section: Discussionsupporting
confidence: 92%
“…In dairy cows, the duration of Cal-Con is influenced by nutritional factors (Tillard et al 2007(Tillard et al , 2008 and the milk yield (Washburn et al 2002;Ansari-Lari et al 2010). The overall mean estimate of Cal-Con found was much higher than 190 days reported for Holstein-Friesian cows in the Ethiopian highlands (Asseged and Birhanu 2004) and 134 days reported for Holstein cows in Iran (Ansari-Lari et al 2010). Characteristically, the Cal-Con reflects the efficiency of estrus detection and has the advantage of allowing early detection of problem cows (Farin and Slenning 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, non significant effects of calving season and calving year on incidence of abortion and stillbirths were reported by Vaccaro and Vaccaro (1982) in Holstein and Brown Swiss crossbred in intensive tropical milk production system, but Adeneye (1982) reported significant effects of parity on abortion and stillbirth incidences of imported Friesians herd in west Nigeria that higher abortions and stillbirths were observed in heifers than cows. The observed overall survival rate (77.5%) of female calves within 365 days of age is comparable with 80.3%, 75%, and 80% of yearling age of survival rate reported by Asseged and Birhanu (2004) in commercial dairy farms in and around Addis Ababa, by Mengesha (1993) at Holeta research station and by AACM (Australian Agricultural Consulting and Management) (1985) in Dairy Rehabilitation and Development Project preparation report, respectively. However, the survival rate found in this study is lower than 87% reported by Fikadu and Tefera (1993) at Adamitulu-Abernosa cattle ranch, but it was higher than that of (70.1%) survival rates of Friesian-Boran crossbred cattle up to 1 year of age reported by Gebeyehu and Hegde (2003) at Cheffa farm.…”
Section: Abortion Stillbirth and Female Calves Survival Ratessupporting
confidence: 86%
“…Also, Asmare and Kiros (2016) showed that incidence of dystocia is three to four times as frequent in females calving for the first time compared to females in the second parity. Thus, Asseged et al (2004) and Bleul (2011) recommended crossing of local breeds of cow at second parity and above with exotic bull to avoid the problem.…”
Section: Discussionmentioning
confidence: 99%